The immune mechanisms of acute exacerbations of idiopathic pulmonary fibrosis - Chen, Tao; Sun, Wei; Xu, Zuo-jun (Frontiers in Immunology, 2024)
Acute exacerbations of idiopathic pulmonary fibrosis (AE-IPF) are the leading cause of mortality among patients with IPF. There is still a lack of effective treatments for AE-IPF, resulting in a hospitalization mortality rate as high as 70%–80%. To reveal the complicated mechanism of AE-IPF, more attention has been paid to its disturbed immune environment, as patients with IPF exhibit deficiencies in pathogen defense due to local immune dysregulation. During the development of AE-IPF, the classical stimulatory signals in adaptive immunity are inhibited, while the nonclassical immune reactions (Th17) are activated, attracting numerous neutrophils and monocytes to lung tissues. However, there is limited information about the specific changes in the immune response of AE-IPF. We summarized the immune mechanisms of AE-IPF in this review.